2017
DOI: 10.1002/stem.2594
|View full text |Cite|
|
Sign up to set email alerts
|

Quaking Is a Key Regulator of Endothelial Cell Differentiation, Neovascularization, and Angiogenesis

Abstract: The capability to derive endothelial cell (ECs) from induced pluripotent stem cells (iPSCs) holds huge therapeutic potential for cardiovascular disease. This study elucidates the precise role of the RNA‐binding protein Quaking isoform 5 (QKI‐5) during EC differentiation from both mouse and human iPSCs (hiPSCs) and dissects how RNA‐binding proteins can improve differentiation efficiency toward cell therapy for important vascular diseases. iPSCs represent an attractive cellular approach for regenerative medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 56 publications
0
58
1
Order By: Relevance
“…As both miR-200c and miR-375 act both on the mRNA level and on translation of QKI-5, this ZEB1/miR-200/miR-375/QKI-5 regulatory loop is particularly strong, producing the strongly mesenchymal expression pattern of QKI we observed in the panel of breast cancer cell lines that we examined, paralleling the mutually exclusive expression of miR-200c and ZEB1 . Since QKI has notable functions outside of EMT, including regulating neuronal (Larocque et al, 2005;Zhao et al, 2006;Hayakawa-Yano et al, 2017), smooth muscle and vascular (Noveroske et al, 2002;Li et al, 2003;van der Veer et al, 2013;Cochrane et al, 2017) cell function, and alternative splicing programmes during muscle cell (Hall et al, 2013) and monocyte (de Bruin et al, 2016a) differentiation, we propose that the ZEB1/miR-200c/miR-375/QKI-5 pathway may influence splicing outcomes that impact a broad range of cell differentiation contexts.…”
Section: Discussionmentioning
confidence: 99%
“…As both miR-200c and miR-375 act both on the mRNA level and on translation of QKI-5, this ZEB1/miR-200/miR-375/QKI-5 regulatory loop is particularly strong, producing the strongly mesenchymal expression pattern of QKI we observed in the panel of breast cancer cell lines that we examined, paralleling the mutually exclusive expression of miR-200c and ZEB1 . Since QKI has notable functions outside of EMT, including regulating neuronal (Larocque et al, 2005;Zhao et al, 2006;Hayakawa-Yano et al, 2017), smooth muscle and vascular (Noveroske et al, 2002;Li et al, 2003;van der Veer et al, 2013;Cochrane et al, 2017) cell function, and alternative splicing programmes during muscle cell (Hall et al, 2013) and monocyte (de Bruin et al, 2016a) differentiation, we propose that the ZEB1/miR-200c/miR-375/QKI-5 pathway may influence splicing outcomes that impact a broad range of cell differentiation contexts.…”
Section: Discussionmentioning
confidence: 99%
“…1C,D). Our laboratory has recently reported that the RBP QKI-5 holds a key role in EC differentiation, angiogenesis and neovascularisation (Cochrane et al, 2017). Since the field of RBPs is fast emerging, and RBPs are now recognised as powerful, versatile regulatory units, which play pivotal roles in the regulation of cell differentiation (Guallar and Wang, 2014), we hypothesised that QKI alternative splicing may play a role in determining the developmental fate of the vascular cell.…”
Section: Qki-6 Is Induced During Vsmc Differentiation Mediated By Pbgmentioning
confidence: 98%
“…QKI alternative splicing isoform (QKI-5) has recently been identified by our laboratory to direct iPSC differentiation to an endothelial lineage through direct binding and stabilisation of STAT3, while iPS-ECs overexpressing QKI-5 enhanced repair in an in vivo model of hind limb ischaemia (Cochrane et al, 2017). Notably, QKI has been shown to be strongly induced in vascular injury, altering the expression of myocardin, a key driver of VSMC differentiation (van der Veer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no doubt that miR-208-regulated QKI defines the phenotypic plasticity of the vascular smooth muscle cells (van der Veer et al, 2013;Cochrane et al, 2017). These functional pieces of evidence of the involvement of QKI into the development of cardiovascular conditions are also supported by the GWAS, which pointed at QKI as a contributor to coronary heart disease (Dehghan et al, 2016).…”
Section: Discussionmentioning
confidence: 86%